DEVELOPMENT OF LKPD MODEL DISCOVERY LEARNING ACTIVITY ORIENTED CRITICAL THINKING ON VIBRATION MATERIALS, WAVES, AND SOUND FOR LEARNING IPA CLASS VIII IN JUNIOR HIGH SCHOOL 13 PADANG - ari ari senita; Amali Putra (Universe, 2021)
Critical thinking activity, is one of the capabilities of the 21st century that wants to be accomplished in learning with scientific approaches through the teaching materials used by teachers. One of the recommended learning models is the Discovery Learning model, and the teaching material used by the teacher is the Learners ' worksheet (LKPD). The problem is, how is the form of Model Discovery Learning LKPD that can be developed for the learning IPA SMP/MTs in the city of Padang? This research aims to produce the LKPD Discovery Learning model to develop the students ' critical thinking activities on vibration, wave, and sound materials for SMP/MTs SCIENCES in Padang City through a method of Research and Development (R&D), by implementing models 4-D (Define, Design, Develop, and Dessiminate) that are reduced to the stage of Develop). The products produced in this research in the form of model LKPD DL activity oriented critical thinking after being validated by expert judgment consisting of 3 lecturers of SCIENCE education faculty and 1 teacher of IPA study with an average score of 88.61% on valid category.